The Discourse of Parents’ Competency in Upbringing in Latvian Media Space (2004–2016) - Medne, Dace; Jansone-Ratinika, Nora; Dinka, Ilze (Acta Paedagogica Vilnensia, 2017)
The sociopolitical situation in Latvia after joining the European Union in 2004 promoted changes in the society and, as a consequence, substantiated the necessity for the transformation of views and processes in the family as well. This situation initiated the search for and the definition of the new focus within upbringing in the family, all the while stating the dominating discourses both in theory and practice. The change of topical trends also stimulated the discussion on the implementer of the upbringing discourse – the parents – the content and form of the competency in upbringing, thus stating the relevant emphases within the actual situation. This article introduces the analysis of the parents’ competency in upbringing, revealed in the printed medium Mans Mazais (“My Little One”) – a significant and stable promoter of the upbringing discourse among parents and future parents in Latvia since 1994 – with the aim to identify and portray the dominant parenting approaches.